INTERNAL AND EXTERNAL ANALYSIS OF RSUD H. ABDUL AZIZ MARABAHAN PREPARATION IN IMPLEMENTING BADAN LAYANAN UMUM DAERAH - Candra Wijaya; Basu Swastha Dharmmesta (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Minister of Domestic Affair’s Rules No. 61/2007 gives an opportunity to H. Abdul Aziz Marabahan (HAAM) Hospital to be Regional Public Service Institution (Badan Layanan Umum Daerah) which has greater authonomy on financial management. In the process of converting the status, analysis concerning internal and external condition were done to know the strategic factors in customizing alternative implementation strategies of BLUD. Research method was a case analysis using descriptive qualitative method. The analytical tools used were IFAS, EFAS, SFAS and SWOT Matrix. The respondents were internal staffs of the hospital and stakeholder as the external part of it. Research result of IFAS, EFAS and SFAS analysis showed that HAAM Hospital strongly responded its internal factors with higher score above the average ability of similar institutions. Hospital also had capability in using opportunity optimally. Result of SWOT analysis showed 4 alternative strategies. SO strategies are the use of monitoring team to accelerate the implementation of BLUD, the use of stakeholder’s support to get funds and subsidiaries and the strategy to coordinate with examiner team about final requirements of BLUD. ST strategy consisted of the use of monitoring team of BLUD on the arrangement of hospital financial licence, the strategy in implementing hospital status as an attempt to improve the service quality. WO strategies are the use of stakeholder’s support to provide more hospital facilities, the strategy to raise the willingness of hospital staff to work and the strategy to adapt its rate to motivate the employees. WT strategies covered the use of existed facilities and human resources to manage the finance of BLUD and Jamkesmas and the strategy to hold on the MoU of specialist visits in keeping society’s trust. Key words: Alternative strategy, Badan Layanan Umum Daerah, H. Abdul Aziz Marhabaan Hospital